El Excentrico, 1971-12-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
December 5, 1971 [5 de diciembre de 1971]. No issue or volume number. Cover has a photograph of three women from the band Chelo y su conjunto next to a stage.